ANALISIS KOMPARASI KINERJA KEUANGAN PT. MNC KAPITAL INDONESIA TBK SEBELUM DAN SESUDAH DILAKUKAN PROSES AKUISISI - Vidian, Clara Sari; Rudianto, Dudi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Not a few companies have gone bankrupt or are unable to survive in the current era, and in order to avoid this, the company must carry out a business strategy. The purpose of this research is to find out and analyze whether there are differences in the performance of PT MNC Kapital Indonesia Tbk companies both before and after the management has carried out the acquisition strategy. The method for analyzing the financial performance of the company PT MNC Kapital Indonesia Tbk both before and after the acquisition uses the financial ratio method which consists of the ratios of liquidity, activity, solvency to profitability and market value (sensitivity to market). The results of this study, namely that there is a significant difference in the financial performance of PT MNC Kapital Indonesia in terms of the activity ratio before and after the acquisition. The FATO ratio indicator has decreased, while the TATO and WCTO ratios have increased after management made the acquisition. A significant difference in the financial performance of PT MNC Kapital Indonesia is reviewed based on the solvency ratio before and after the acquisition. The ratio indicators DAR, DER and LRTD decreased after management carried out the acquisition policy, which is significant in PT MNC Kapital Indonesia's financial performance in terms of profitability ratios before and after the acquisition.